Analisis Keuntungan Usahatani Jeruk Siam Pada Lahan Gambut Di Kecamatan Betara, Kabupaten Tanjung Jabung Barat - Dalas, Ici; Edison, Edison; Muchlis, Fuad (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2022)
Siam orange production in Jambi Province in 2019 was 372,516 quintals, with an average yield per hectare of 54.85 quintals with a harvested area of 946.20 hectares. Of this number, Tanjung Jabung Barat Regency in 2019 was the third largest Siamese orange producing area in Jambi Province, with a production of 102,609 quintals. The limitations of production cost factors as input allocation will affect profits in Siam Orange farming optimally so that from this situation farmers are faced with the choice of using farming resources and are required to implement limited resource efficiency efforts so that they are profitable in Siam Orange farming.The purpose of this study was to determine the general description of farming, the magnitude of the profits obtained from farming and to analyze the factors that influence the profits of Siamese citrus farming. The research location is in Betara District, Tanjung Jabung Barat Regency. The analysis used to analyze the profit of farming is descriptive quantitative analysis. and to analyze profits with the Cobb-Douglas function, and analysis of R/C ratio. General description of Siamese citrus farming on peat land in the research location, harvest duration 2 times know the cost of production Rp. Rp.17.556.054/tahun, with big profits Siam citrus farming research location Rp. 109.005.546 /tahun. Cobb Douglas function coefficient test Production factors, land rent costs, fertilizer costs, labor costs, pesticide costs and depreciation costs partially affect the profits of Siamese citrus farming on peatlands. Land rental costs, fertilizer costs and depreciation costs have a positive effect on profits, while labor costs and pesticide costs have a negative effect on the profits of Siamese citrus farming on peat land.